Genetic variation in the familial Mediterranean fever gene (MEFV) and risk for Crohn's disease and ulcerative colitis. - Alexandra-Chloé Villani; Mathieu Lemire; Edouard Louis; Mark S Silverberg; Catherine Collette; Geneviève Fortin; Elaine R Nimmo; Yannick Renaud; Sébastien Brunet; Cécile Libioulle; Jacques Belaiche; Alain Bitton; et al. (PLoS ONE)
Background and aims The familial Mediterranean fever (FMF) gene (MEFV) encodes pyrin, a major regulator of the inflammasome platform controlling caspase-1 activation and IL-1beta processing. Pyrin has been shown to interact with the gene product of NLRP3, NALP3/cryopyrin, also an important active member of the inflammasome. The NLRP3 region was recently reported to be associated with Crohn's disease (CD) susceptibility. We therefore sought to evaluate MEFV as an inflammatory bowel disease (IBD) susceptibility gene. Methodology and results MEFV colonic mucosal gene expression was significantly increased in experimental colitis mice models (TNBS p<0.0003; DSS p<0.006), in biopsies from CD (p<0.02) and severe ulcerative colitis (UC) patients (p<0.008). Comprehensive genetic screening of the MEFV region in the Belgian exploratory sample set (440 CD trios, 137 UC trios, 239 CD cases, 96 UC cases, and 107 healthy controls) identified SNPs located in the MEFV 5' haplotype block that were significantly associated with UC (rs224217; p = 0.003; A allele frequency: 56% cases, 45% controls), while no CD associations were observed. Sequencing and subsequent genotyping of variants located in this associated haplotype block identified three synonymous variants (D102D/rs224225, G138G/rs224224, A165A/rs224223) and one non-synonymous variant (R202Q/rs224222) located in MEFV exon 2 that were significantly associated with UC (rs224222: p = 0.0005; A allele frequency: 32% in cases, 23% in controls). No consistent associations were observed in additional Canadian (256 CD trios, 91 UC trios) and Scottish (495 UC, 370 controls) sample sets. We note that rs224222 showed marginal association (p = 0.012; G allele frequency: 82% in cases, 70% in controls) in the Canadian sample, but with a different risk allele. None of the NLRP3 common variants were associated with UC in the Belgian-Canadian UC samples and no significant interactions were observed between NLRP3 and MEFV that could explain the observed flip-flop of the rs224222 risk allele. Conclusion The differences in association levels observed between the sample sets may be a consequence of distinct founder effects or of the relative small sample size of the cohorts evaluated in this study. However, the results suggest that common variants in the MEFV region do not contribute to CD and UC susceptibility.